Transition of a Large Tertiary Heart Failure Program in Response to the COVID-19 Pandemic: Changes That Will Endure. (September 2020) - Sayer, Gabriel; Horn, Evelyn M.; Farr, Maryjane A.; Axsom, Kelly; Kleet, Audrey; Gjerde, Cecilie; Latif, Farhana; Sobol, Irina; Kelley, Nancy; Lancet, Erica; Halik, Carolyn; Takeda, Koji; et al.
Abstract : The coronavirus disease 2019 (COVID-19) pandemic imposed severe restrictions on traditional methods of patient care. During the pandemic, the heart failure program at New York-Presbyterian Hospital in New York, NY rapidly and comprehensively transitioned its care delivery model and administrative organization to conform to a new healthcare environment while still providing high-quality care to a large cohort of patients with heart failure, heart transplantation, and left ventricular assist device. In addition to the widespread adoption of telehealth, our program restructured outpatient care, initiating a shared clinic model and introducing a comprehensive remote monitoring program to manage patients with heart failure and heart transplant. All conferences, including administrative meetings, support groups, and educational seminars were converted to teleconferencing platforms. Following the peak of COVID-19, many of the new changes have been maintained, and the program structure will be permanently altered as a lasting effect of this pandemic. In this article, we review the details of our program's transition in the face of COVID-19 and highlight the programmatic changes that will endure.